Evaluación de sistemas de labranza y fertilización nitrogenada para agricultura de conservación en el cultivo de maíz variedad Iniap-111 en el Laguacoto II, cantón Guaranda, provincia Bolívar - Guaman Llumitaxi, Daysi Nataly (2021)
Global maize cultivation is among the four staple foods for their contribution to food security and sovereignty. In Ecuador, soft maize cultivation is concentrated in the high land and is the main component of production systems (PS). Bolivar Province is the largest producer of soft maize with 36%. However, due to several adverse factors such as Climate Change (CC), deterioration of natural resources, genetic erosion, conventional farm-intensive monocultures and high dependence on external inputs, they seriously jeopardize the sustainability of local PS. This research process of the implementation of Conservation Agriculture (CA), was carried out for the third year in the Laguacoto II Experimental Farm of Bolivar State University, being its objectives: (i) Evaluate five Tillage Systems (TS) with and without Ecoabonaza on the main agronomic components of the maize variety INIAP 111. (ii) Measure the effect of four doses of Nitrogen (N) on the yield of maize INIAP 111 and (iii) Perform the Partial Budget Economic Analysis (AEPP) and Marginal Rate of Return (TMR). Random Complete Block Design was applied in factorial arrangement and Split Plot. Factor A corresponded to five TS with and without Ecoabonaza, and these were large or major plots and Factor B subplots with four doses of N in kg/ha. Corresponding variance analyses, 5% Tukey test for TL and interactions, Polynomial Trends test for N doses, correlation, linear regression, AEPP and TMR were performed. The main statistical and economic results were different from those reported in the first two years of study perhaps due to the obvious CC. Highly significant differences in the main factors were determined: Tillage Systems and N Doses on maize and biomass yield. For the N, responses with greater linear and quadratic force were mainly presented. Significant dependence on major factors was estimated especially for maize and biomass yield. In the third year of this study, there was no evidence of a significant economic effect of Ecoabonaza, which will be medium and long term. The main agronomic components that contributed to increasing maize yield were doses of N, plant height, biomass, stem diameter, percentage of plants with two ears, length of ear and percentage of grain first. Economically the best technological options for the agroecological area of Laguacoto were the treatments T10: A3B2 (wide bed + 40 kg/ha of N) and the T11: A3B3 (wide bed + 80 kg/ha of N) with TMR values of 365 and 156% respectively. Finally, and in this third year of the research process of the implementation of AC the most important technological components to contribute to improve the productivity of soft maize PS were: INIAP 111 variety maize, TL in a wide bed and depending on the chemical analysis of the soil and the rotation of crops apply the N between 40 and 80 kg/ha split at three times: 30; 60 and 90 days after planting.